Action Taken Report on the Revised Long-Term Action Plan for the KBK Districts of Orissa - Planning Commission (Planning Commission Government of India, 2002)
The Revised Long-Term Action Plan (RLTAP) for the KBK districts of Orissa, covering Kalahandi, Bolangir, Koraput, Nuapada, Sonepur, Nabarangpur, Malkangiri, and Rayagada, was implemented to address entrenched poverty and improve living conditions. With a total budget of Rs. 6061.83 crore (1998-99 to 2006-07), the plan focused on sectors such as agriculture, health, rural connectivity, and welfare for Scheduled Castes and Scheduled Tribes. Key interventions included the Rice Minikit Scheme, integrated crop development programs, mobile health units, watershed management, and the Pradhan Mantri Gram Sadak Yojana. Despite gradual progress, implementation faced challenges due to delayed fund releases, socio-economic barriers, and operational limitations. The report highlights the need for sustained commitment, strategic resource utilization, and community participation to enhance infrastructure, social services, and agricultural productivity, thereby achieving long-term development and poverty alleviation in the KBK region.
Planning Commission Government of India New Delhi February 2002
Keywords: KBK Districts; Revised Long-Term Action Plan; Poverty Alleviation; Rural Development; Agriculture Initiatives; Health Programs; Watershed Management; Rural Connectivity; Scheduled Castes; Scheduled Tribes; Financial Allocation